Nickel-catalyzed difunctionalization of alkynyl bromides with thiosulfonates and N-arylthio succinimides: a convenient synthesis of 1,2-thiosulfonylethenes and 1,1-dithioethenes - Kumari, Arram Haritha; Kumar, Jangam Jagadesh; Krishna, Gamidi Rama; Reddy, Raju Jannapu (Synthesis-Stuttgart, 2021)
An efficient nickel-catalyzed vicinal thiosulfonylation of 1bromoalkynes with thiosulfonates in the presence of cesium carbonate is described. An operationally simple and highly regioselective atom transfer radical addition (ATRA) of alkynyl bromides provides a wide range of (E)-1,2-thiosulfonylethenes (alpha-aryl-beta-thioarylvinyl sulfones) in moderate to high yields. The extensive substrate scope of both alkynyl bromides and thiosulfonates is explored with a broad range of functional groups. Indole-derived 1,1- bromoalkenes were also successfully explored in this 1,2-thiosulfonylation process. Moreover, the nickel-catalyzed geminal- dithiolation of alkynyl bromides with N-arylthio succinimides provides 1,1-dithioalkenes in high yields. The present protocol is reliable on gram scale, and a sequential one-pot bromination and thiosulfonylation of phenylacetylene is achieved in a scale-up synthesis. Following control experiments, a plausible mechanism is proposed to rationalize the experimental outcome and the vicinal thiosulfonylation.
Keywords: alkynyl bromides; atom transfer radical addition (ATRA); thiosulfonates; thiosulfonylation; vinyl thiosulfones